Interaction Energy Surfaces for Li(2(2)S) and Li (2(2)P) With H(2) - Krauss, M. (J Res Natl Bur Stand A Phys Chem, 1968)
Interaction energy surfaces for the interaction of Li(2(2)S) and Li(2(2)P) with H(2) are calculated using approximate Hartree-Fock trial functions. The crossing of energy curves is observed for C(2v) conformations if the H(2) internuclear distance is sufficiently large. No crossing is observed for colinear collissions for any H(2) distance. The wave function of the strongly attractive state involved in the crossing is related to the metastable negative-ion states that are postulated to account for resonant electron-molecule scattering. Such a charge-transfer state can only be bound for C(2v) conformations for the H(2) molecule. The likelihood and geometry of the crossing complexes for other molecules interacting with alkalis is discussed in terms of the formation of these resonance charge-transfer states.